2011
DOI: 10.1111/j.1755-0998.2010.02972.x
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and characterization of single nucleotide polymorphisms in Chinook salmon, Oncorhynchus tshawytscha

Abstract: Molecular population genetics of non-model organisms has been dominated by the use of microsatellite loci over the last two decades. The availability of extensive genomic resources for many species is contributing to a transition to the use of single nucleotide polymorphisms (SNPs) for the study of many natural populations. Here we describe the discovery of a large number of SNPs in Chinook salmon, one of the world's most important fishery species, through large-scale Sanger sequencing of expressed sequence ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 43 publications
3
48
0
1
Order By: Relevance
“…Estimates of The genetic baseline described here was designed primarily to identify fi sh caught in PFMC ocean fi sheries and in ecological investigations in the southern portion of the California Current ecosystem and its associated tributary rivers and streams. We have shown that it performs well in this area but, because of an ascertainment strategy during SNP discovery that included individuals from the Columbia River and British Columbia (Clemento et al, 2011), the baseline also has suffi cient statistical power to identify the source of some fi sh from elsewhere in the North American range of this species. We observed high rates of self-assignment to reporting unit for all regions represented in the baseline, although some reporting units clearly were composed of populations with minimal differentiation from each other.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Estimates of The genetic baseline described here was designed primarily to identify fi sh caught in PFMC ocean fi sheries and in ecological investigations in the southern portion of the California Current ecosystem and its associated tributary rivers and streams. We have shown that it performs well in this area but, because of an ascertainment strategy during SNP discovery that included individuals from the Columbia River and British Columbia (Clemento et al, 2011), the baseline also has suffi cient statistical power to identify the source of some fi sh from elsewhere in the North American range of this species. We observed high rates of self-assignment to reporting unit for all regions represented in the baseline, although some reporting units clearly were composed of populations with minimal differentiation from each other.…”
Section: Discussionmentioning
confidence: 99%
“…We compiled a list of 192 TaqMan (Life Technologies Corp., Carlsbad, CA), or 5'-nuclease, SNP genotyping assays from previously published discovery studies (Smith et al, 2005a(Smith et al, , 2005bCampbell and Narum, 2008;Narum et al, 2008;Clemento et al, 2011) to test their scorability and power for GSI. TaqMan technology combines standard PCR primers that target the genomic region around a SNP with 2 different fl uorescent probes that identify the 2 nucleotide bases present at the SNP.…”
Section: Markers and Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, SNP data is used on a regular basis to predict the stock composition of the world's largest salmon fishery, for sockeye salmon (O. nerka) migrating into Bristol Bay (Habicht et al 2010). The ability of GSI with SNPs to resolve both broad-and fine-scale population structure for ChS across its native range (Clemento et al 2011;Hess et al 2011;Templin et al 2011), as well as to identify the composition of ocean mixtures (Habicht et al 2010;Larson et al 2012;Satterthwaite et al 2014), has been well documented. In this paper, we use GSI to identify the origin of ChS spawning in the Santa Cruz River Basin in Argentina.…”
Section: Introductionmentioning
confidence: 99%
“…Though genetic stock identification techniques based on allele frequencies would not be sufficient to accurately identify the run type and origin of individuals at the FRH (Banks et al 2000;Williamson and May 2005;Garza and Pearse 2008), recent work with single nucleotide polymorphisms (SNPs) has demonstrated the possibility of using a genetics-based method to determine the origin and run type of FRH-produced fish (Clemento et al 2011). Parentage-based tagging using SNPs is a method that requires not only genotyping of the parent broodstock, but also the genotyping and parentage analysis of returning offspring (Anderson and Garza 2006).…”
Section: Introductionmentioning
confidence: 99%